2011
DOI: 10.1016/j.nedt.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' perceived knowledge and attitude towards genetics

Abstract: The purpose of this study was to assess the knowledge base of nursing students regarding the topic of genetics and how this may change as a student progresses through the nursing program. A 70 item multiple-choice and dichotomous survey was given to freshman, sophomore, junior, and senior nursing students at a university school of nursing in the eastern part of the United States. Two hundred and seventy five pre-licensure nursing students, 255 females and 18 males, comprised the sample. A one-way analysis of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
33
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 12 publications
8
33
1
1
Order By: Relevance
“…A U.S. study demonstrated senior nursing students (4th year) having a greater perceived knowledge of genetic terms than either freshman (1st year), sophomore (2nd year) or junior (3rd year) nursing students. [19] The students in this study did not have a stand-alone course but basic genetic content was covered in the biology class and integrated in some of the nursing courses in the advanced nursing levels. [19] The findings of this current study support that educational processes lead to knowledge gain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A U.S. study demonstrated senior nursing students (4th year) having a greater perceived knowledge of genetic terms than either freshman (1st year), sophomore (2nd year) or junior (3rd year) nursing students. [19] The students in this study did not have a stand-alone course but basic genetic content was covered in the biology class and integrated in some of the nursing courses in the advanced nursing levels. [19] The findings of this current study support that educational processes lead to knowledge gain.…”
Section: Discussionmentioning
confidence: 99%
“…[19] The students in this study did not have a stand-alone course but basic genetic content was covered in the biology class and integrated in some of the nursing courses in the advanced nursing levels. [19] The findings of this current study support that educational processes lead to knowledge gain. As previously stated, the singular didactic genetics course was developed, at the beginning of the students' educational process, to establish the basis for the comprehension of genetic content, with an assumption that the furthering of this knowledge would occur as the student progressed through the curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Dodson & Lewallen, 2011;Hsiao et al, 2011;Iino et al, 2002;Maradiegue et al, 2005;Vural et al, 2009) Table 5). …”
mentioning
confidence: 99%